Strengthening programming skills among engineering students through experiential learning based robotics project - Mohd Faisal Ibrahim; Aqilah Baseri Huddin; Fazida Hanim Hashim; Mardina Abdullah; Ashrani Aizzuddin Abd Rahni; Seri Mastura Mustaza; Aini Hussain; Mohd Hairi Mohd Zaman (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study examined the educational effects in strengthening programming skills among university’s undergraduate engineering students via integration of a robotics project and an experiential learning approach. In this study, a robotics project was conducted to close the gap of students’ difficulty in relating the theoretical concepts of programming and real-world problems. Hence, an experiential learning approach using the Kolb model was proposed to investigate the problem. In this project, students were split into groups whereby they were asked to develop codes for controlling the navigation of a wheeled mobile robot. They were responsible for managing their group’s activities, conducting laboratory tests, producing technical reports and preparing a video presentation. The statistical analysis performed on the students’ summative assessments of a programming course revealed a remarkable improvement in their problem-solving skills and ability to provide programming solutions to a real-world problem.